To the question of correction of Parkinson's disease by means of physical therapy - Labinsky, Andriy (Journal of Education, Health and Sport, 2017)
Topicality. Determining the level of effectiveness of the use of physical therapy in the early stages of Parkinson's disease to stop the rate of its progression. Objectives of the study: to develop and apply to patients with Parkinson's disease in the early stages with predominantly non-motor manifestations physical therapy program. To study the effectiveness of the developed physical therapy program on the scale of assessment of the state of non-motor symptoms, mental disorders and cognitive impairment in Parkinson's disease. Research results. After the physical therapy, the patients' condition improved significantly. Cognitive, mental functions, motor abilities and manifestations from the side of the cardiovascular system are effectively improved with the help of physical exercises and the whole complex of physical therapy we have developed. Changes in the status of patients after physical therapy for the better were recorded by both subjective and objective survey data. Particularly significant were the data from the study on the scale of assessment of patients with non-motor manifestations of Parkinson's disease (scale of non-motor symptoms – NMSS, scale of mental disorders – MMSE, Montreal scale of cognitive disorders-MOCA). They showed a significant statistically significant difference between the control and the main group of patients towards improvement in the final examination. Conclusions. According to research data, the condition of patients who received the physical therapy complex was significantly better than in the group of patients who did not receive physical therapy, indicates the effectiveness of the developed and used complex physical therapy for non-motor manifestations of Parkinson's disease and allows us to recommend it for widespread use.